THE EFFECT OF WORK ENVIRONMENT AND COMPENSATION ON TEACHER’S JOB SATISFACTION AT STATE SENIOR HIGH SCHOOL 27 BANDUNG - Anton Budi Santoso; Rahmani Almaida (SEAN Institute, 2023)
This study's objective is to determine the extent to which work environment and salary impact teacher job satisfaction at State Senior High School 27 Bandung. In this study, quantitative research methodologies are used with descriptive research techniques. This study's participants were all teachers at State Senior High School 27 Bandung. The sampling approach employed is the census method, therefore 73 individuals represent the whole population. Questionnaires were employed to collect primary data, and IBM SPSS Version 26 was utilized to analyze the questionnaire results. The findings of this study suggest that the work environment has only a marginal effect on job satisfaction. Compensation has a big impact on job satisfaction in part. The work environment and salary have a major impact on job satisfaction simultaneously.